Analysing User Reviews with ETL using Pentaho Data Integration - Tri Luhur Indayanti Sugata; Rafika Rahmawati; Tri Puspa Rinjeni; Virdha Rahma Aulia; Prasasti Karunia Farista Ananto; Iqbal Ramadhani Mukhlis (LKP KARYA PRIMA KURSUS, 2025)
User reviews are a crucial element in guiding the continuous improvement of mobile applications for developers. This research aims to utilize Extract, Transform, Load (ETL) techniques using Pentaho Data Integration to analyze user reviews of government mobile applications which is ‘Sentuh Tanahku’, focusing on improving service quality through actionable data insights. The ETL process involves collecting and cleaning data from the Google Play Store to derive valuable insights that inform recommendations for app improvement. After data extraction, text preprocessing steps, such as cleansing, case folding, and keyword filtering, were applied to prepare the data for analysis. By categorizing user reviews into key aspects such as user interface, performance, bug fixes, security, compatibility and feature development this research enables the identification of most frequently discussed and complained about by users. The output of this research includes a structured dataset in Excel format. By demonstrating the effectiveness of ETL and text analysis in transforming unstructured user reviews into strategic insights, this research contributes to utilizing Pentaho Data Integration as an alternative and effective tool for processing and analyzing user reviews.